In vitro Antioxidant, Membrane Stabilizing and Thrombolytic Activities of Glycosmis arborea - Hossain, Sayed Mamur; Islam, Farhana; Sharmin, Tasnuva; Sheikh, Hasib; Hasan, AM Rashedul; Rashid, Mohammad A (Bangladesh Pharmaceutical Journal, 2012)
The methanol extract of leaves and stems of Glycosmis arborea and their pet-ether, carbon tetrachloride, chloroform and aqueous soluble partitionates were subjected to assays for antioxidant activity by Folin-Ciocalteau reagent, membrane stabilizing and thrombolytic activities. The carbon tetrachloride soluble fraction of stems of G. arborea demonstrated the presence of significant amount of phenolic compounds (36.95 ± 0.54 mg of GAE/g of extract). The extractives inhibited heat as well as hypotonic solution-induced haemolysis of rat erythrocytes in vitro. The pet-ether soluble fraction of leaves and stems of G. arborea showed 20.46 and 38.24% and 22.50 and 48.25%. inhibition of hemolysis of RBC caused by heat and hypotonic solution, as compared to 30.55 and 72.91% inhibition of hemolysis of RBC caused by the standard Acetyl salicylic acid at 0.01 mg/ml concentration, respectively. Among the four fractions, the chloroform soluble materials of the stems of G. arborea revealed highest thrombolytic activity with clot lysis value of 36.50% while standard streptokinase and water used as positive and negative controls, showed 64.25±0.26 and 2.35±0.35 % lysis of clot respectively DOI: http://dx.doi.org/10.3329/bpj.v15i2.12579 Bangladesh Pharmaceutical Journal 15(2): 141-143, 2012